2017
DOI: 10.5546/aap.2017.eng.43
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional assessment of a population with a history of childhood craniopharyngioma seen at Hospital “Prof. Dr. Juan P. Garrahan”

Abstract: Introduction.Craniopharyngiomas are histologically benign malformations located between the pituitary and hypothalamus that may affect key hormone secretion for endocrine regulation and satiety modulation. Although this is a relatively benign disease, the combination of severe hypothalamic obesity and associated comorbidities results in a reduced quality of life. Objective. To assess the nutritional status of patients after craniopharyngioma surgery. Population and Methods. Patients younger than 21 years old a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…REE was shown to be lower in CP patients compared to children with multifactorial obesity regardless of the amount of fat-free mass or when compared to matched controls ( 18 ). In another study, CP patients were shown to have a 17% lower REE value compared to the values that were expected from the WHO equation ( 49 ). Our study results confirm that REE may be lowered in children with hypothalamic damage and shows that this is associated to the degree of clinical HD (in the multivariate analysis), as well as to radiological posterior hypothalamic damage (in the univariate analysis).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…REE was shown to be lower in CP patients compared to children with multifactorial obesity regardless of the amount of fat-free mass or when compared to matched controls ( 18 ). In another study, CP patients were shown to have a 17% lower REE value compared to the values that were expected from the WHO equation ( 49 ). Our study results confirm that REE may be lowered in children with hypothalamic damage and shows that this is associated to the degree of clinical HD (in the multivariate analysis), as well as to radiological posterior hypothalamic damage (in the univariate analysis).…”
Section: Discussionmentioning
confidence: 86%
“…To our knowledge, this is the first study in which REE measurements of children with brain injury at risk of HD have been associated with scores for clinical HD and radiological hypothalamic damage. Previous cohort studies have examined REE measurements in children with brain injury and compared them to obese children without brain injury or compared REE measurements in normal weight craniopharyngioma (CP) patients with those in obese CP patients ( 15 , 18 , 49 , 50 , 51 , 52 ). REE was shown to be lower in CP patients compared to children with multifactorial obesity regardless of the amount of fat-free mass or when compared to matched controls ( 18 ).…”
Section: Discussionmentioning
confidence: 99%